2007
DOI: 10.1007/s00726-007-0607-z
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic effects of leucine and glutamine on the mTOR pathway in myogenic C2C12 cells

Abstract: This study compared the effects of leucine and glutamine on the mTOR pathway, on protein synthesis and on muscle-specific gene expression in myogenic C(2)C(12) cells. Leucine increased the phosphorylation state of mTOR, on both Ser2448 and Ser2481, and its downstream effectors, p70(S6k), S6 and 4E-BP1. By contrast, glutamine decreased the phosphorylation state of mTOR on Ser2448, p70(S6k) and 4E-BP1, but did not modify the phosphorylation state of mTOR on Ser2481 and S6. Whilst the phosphorylation state of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 25 publications
7
42
0
Order By: Relevance
“…However, a study by Averous et al (2014), reports that mTORC1 activity does not correlate with its lysosomal localization in serum-fed cells. Other mechanisms for glutamine regulation of mTORC1 have been proposed, including increasing the influx of leucine via the heterodimeric cotransporter SLC7A5-SLC3A2 (Nicklin et al 2009), increasing the levels of a-ketoglutarate (Yao et al 2012), and decreasing Akt activity (Deldicque et al 2008). The results of our biochemical evaluation of several pathways known to regulate mTOR did not reveal a clear candidate signaling pathway that was responsible for the observed effects.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…However, a study by Averous et al (2014), reports that mTORC1 activity does not correlate with its lysosomal localization in serum-fed cells. Other mechanisms for glutamine regulation of mTORC1 have been proposed, including increasing the influx of leucine via the heterodimeric cotransporter SLC7A5-SLC3A2 (Nicklin et al 2009), increasing the levels of a-ketoglutarate (Yao et al 2012), and decreasing Akt activity (Deldicque et al 2008). The results of our biochemical evaluation of several pathways known to regulate mTOR did not reveal a clear candidate signaling pathway that was responsible for the observed effects.…”
Section: Discussionmentioning
confidence: 57%
“…mTORC1 is a critical cellular energy and nutrient status sensor that integrates signals from multiple pathways to regulate protein, lipid, and nucleotide synthesis, and it has also been identified as an important modulator of learning and memory (Dash et al 2006;Gkogkas et al 2010;Hoeffer and Klann 2010;Graber et al 2013;Santini et al 2014). Previous studies using cultured cells deprived of serum/amino acids have shown that glutamine can either increase or decrease mTORC1 activity (Deldicque et al 2008;Nicklin et al 2009;Kim et al 2013). However, as these in vitro studies were carried out under serumand/or amino acid-deprived culture conditions, the physiological relevance of these findings remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations